Evaluation of the validity of the pre-marriage Mean Corpuscular Volume value as a predictive test for β-thalassemia carrier status - Almomani, Ali; Shraim, Ala'a; Atoom, Ali; Alhmoud, Jehad (Journal of Medical Biochemistry, 2022)
Background: The national mandatory premarital screening test is based on MCV > 80fL value for the detection of β-thalassemia to provide acceptance for marriage. The objective of this study is to assess the efficacy of MCV as a screening test for β-thalassemia trait in the present population. Methods: This study was conducted on 418 blood samples collected from adult individuals. The diagnosis of β‐thalassemia carrier was given to those having HbA2 values equal to or above 3.5%. The diagnostic reliability of different RBC indices and formulas in discriminating cases of β-thalassemia trait were evaluated. Finally, a new index called “Momani” was determined based on MCV, RDW and RBC count. Results: β-thalassemia trait was identified in 10 % of the cases. The measured MCV value was significantly lower in β-thalassemia carrier group compared to non-carrier group (p = <0.001). MCV value and RBC count showed a higher diagnostic reliability than other RBC indices. We found that MCV ≤ 74.45fl is more suitable cut off value of MCV with 86.2% specificity, 71.4% sensitivity, 36.6% positive predictive value, and 96.4% negative predictive value. Finally, our index “Momani” was found to be useful in predicting carrier and paralleled the performance of Sirdah, Mentzer, and Ehsani indices. Conclusion: MCV<80 is a useful but not a perfect cut-off point for the screening of β-thalassemia carriers from non-carriers. The diagnostic accuracy of MCV can be improved by selecting a new cutoff value. Moreover, “Momani” index shows good discrimination ability in diagnosing β -thalassemia carrier in our population.